1973
DOI: 10.1128/aac.3.2.235
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of 1-β- d -Ribofuranosyl-1,2,4-Triazole-3-Carboxamide (Virazole, ICN 1229) on Deoxyribonucleic Acid and Ribonucleic Acid Viruses

Abstract: Virazole (1-β- d -ribofuranosyl-1,2,4-triazole-3-carboxamide) is a highly soluble new synthetic nucleoside having significant, reproducible activity against a broad spectrum of deoxyribonucleic acid and ribonucleic acid viruses in vitro. The drug inhibited viral cytopathogenic effects in monolayers of cells infected for 3 days with type 3 adeno, types 1 and 2 herpes, myxoma, cytomegalo, vaccinia, infectious bovine rhinotracheitis, types 1A, 2, 8, 13, and 56 rhino, types 1 and 3 parainfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(83 citation statements)
references
References 11 publications
6
76
1
Order By: Relevance
“…Additionally, these results are similar to those reported in investigations of other RNA viruses (IC 50 s between 1.6 and 66.7 µg/ml) including orthomyxoviruses (influenza virus) and paramyxoviruses (parainfluenza virus, mumps virus, measles virus, and respiratory syncytial virus) in vitro (Huffman et al, 1973;Shigeta et al, 1992). However, a direct comparison of results is difficult because a variety of methods have been used to assess the effect of ribavirin.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, these results are similar to those reported in investigations of other RNA viruses (IC 50 s between 1.6 and 66.7 µg/ml) including orthomyxoviruses (influenza virus) and paramyxoviruses (parainfluenza virus, mumps virus, measles virus, and respiratory syncytial virus) in vitro (Huffman et al, 1973;Shigeta et al, 1992). However, a direct comparison of results is difficult because a variety of methods have been used to assess the effect of ribavirin.…”
Section: Discussionsupporting
confidence: 74%
“…It is a water-soluble synthetic nucleoside with broad-spectrum antiviral properties that has been shown to be active in vitro against many viruses (Huffman et al, 1973;Gururangan et al, 1990;Honda et al, 1994;Ishii et al, 1996;Chong et al, 2001;Graci & Cameron, 2006;Elia et al, 2008). Although RBV was used as an antiviral agent during the first NiV outbreak in 1999 in Malaysia, its antiviral properties could not be confirmed in the generally accepted hamster model (Georges-Courbot et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ribavirin, a related ribofuranosylcarboxamide, has a broad spectrum of antiviral activity (32), both in vitro (2,14,20,24) and in vivo (13,16,19,31,37), and is currently under clinical evaluation for safety and efficacy in humans. Recent studies have shown that ribavirin is remarkably effective clinically against influenza A and B (17,21), hepatitis (23), and respiratory syncytial virus infection (11).…”
mentioning
confidence: 99%